2009
DOI: 10.1186/1743-422x-6-65
|View full text |Cite
|
Sign up to set email alerts
|

Properties of virion transactivator proteins encoded by primate cytomegaloviruses

Abstract: All of the UL82 homolog proteins analysed activated gene expression, but surprising differences in other aspects of their properties were revealed. The results provide new information on early events in infection with cytomegaloviruses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…However, unlike human pp71, the simian UL82 proteins did not support long-term expression from quiescent HSV-1 genomes, and kinetics were significantly different in both the intranuclear localization of the simian homologs and the effects on Daxx and/or ATRX relocalization (123). Recently, a UL82 homolog encoded by guinea pig cytomegalovirus (GPCMV) was found to stimulate the transfection efficiency of GPCMV DNA and to complement replication of a HSV-1 VP16 mutant.…”
Section: Daxx Impairment By Virion Proteins: Overcoming the Species Bmentioning
confidence: 99%
See 1 more Smart Citation
“…However, unlike human pp71, the simian UL82 proteins did not support long-term expression from quiescent HSV-1 genomes, and kinetics were significantly different in both the intranuclear localization of the simian homologs and the effects on Daxx and/or ATRX relocalization (123). Recently, a UL82 homolog encoded by guinea pig cytomegalovirus (GPCMV) was found to stimulate the transfection efficiency of GPCMV DNA and to complement replication of a HSV-1 VP16 mutant.…”
Section: Daxx Impairment By Virion Proteins: Overcoming the Species Bmentioning
confidence: 99%
“…Other nonhuman primate CMVs encode homologs of HCMV pp71, which efficiently initiate IE viral gene expression (123). However, unlike human pp71, the simian UL82 proteins did not support long-term expression from quiescent HSV-1 genomes, and kinetics were significantly different in both the intranuclear localization of the simian homologs and the effects on Daxx and/or ATRX relocalization (123).…”
Section: Daxx Impairment By Virion Proteins: Overcoming the Species Bmentioning
confidence: 99%
“…Immediate early expression of viral genes is activated by the viral pp71 protein and ND10 is targeted by pp71 for this activation [35,36]. Recent studies have shown that pp71 displaces ATRX from the ND10 and thereby initiates expression of the viral genes [35,36]. On this basis it is tempting to suggest involvement of ATRX in controlling IPNV replication.…”
Section: Discussionmentioning
confidence: 96%
“…cytomegalovirus (HCMV) through repression of the expression of immediate early genes of HCMV [35] by its binding to the nuclear domain 10 (ND10). Immediate early expression of viral genes is activated by the viral pp71 protein and ND10 is targeted by pp71 for this activation [35,36]. Recent studies have shown that pp71 displaces ATRX from the ND10 and thereby initiates expression of the viral genes [35,36].…”
Section: Discussionmentioning
confidence: 98%
“…pp65 is dispensable for virus replication [24] whereas the major impact of pp71 is in viral gene expression where it modulates epigenetic gene regulation by interacting with the host protein DAXX [86]. In summary, HCMV tegumentation confers stability to nucleocapsids and provides a signal for final envelopment through protein-protein interactions that start at the surface of the capsid prior to encapsidation of viral DNA in the nucleus and continue throughout cytoplasmic maturation events.…”
Section: Cytoplasmic Stage Of Hcmv Maturationmentioning
confidence: 99%